Structural modification of gallium lanthanum sulfide glass induced by ultrafast laser inscription - Diener, Romina; Tabacchi, Gloria; Nolte, Stefan; Minardi, Stefano (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
We present a preliminary experimental chemical-physical characterisation of the structural modification of Gallium Lanthanum Sulfide (GLS) glass occurring during ultrafast laser inscription of waveguides in thermal regime. Our measurements with a micro-Raman spectrograph confirmed previous reports of negligible chemical modification of the irradiated glass. Additionally, the observed onset of significant long-range stress patterns surrounding the irradiated regions indicate that GLS is subject to an irradiation-induced densification of the glass network. We discuss the consequences of these observations for the amelioration of the laser inscription techniques in chalcogenide glasses and, potentially, for the understanding of their microscopic structure.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Chalcogenide glasses; structure of glasses; ultrafast laser inscription